STUDI KUALITAS AIR BEBERAPA MATA AIR DI SEKITAR BEDUGUL, BALI (THE STUDY OF WATER QUALITY OF SPRINGS SURROUNDING BEDUGUL, BALI) - I Wayan Arthana (Environmental Research Center (PPLH) of Udayana University)
Spring is source of water that emerges automatically to the surface from theground. Water samples were taken from springs at Gesing village, close to Buyan lakeand at Teratai Bang Temple (PRTB), a temple in the central of Bedugul BotanicalGarden. There were twenty three parameters of water quality measured and twomicrobiological parameters observed. Six of the twenty five parameters observed wereover than standard namely BOD5, COD, Sulfide, Iron, Lead and Cadmium. The contentof BOD5 at three springs (2.03 – 8.10 mg/l) the highest at PRTB and the lowest at Gesingand all are over standard of 2 mg/l. Cadmium that over standard of 0.01 mg/l is inBuyan spring (0.013 mg/l) and at PRTB (0.012 mg/l). The highest iron is in PRTB spring(0.463 mg/l) that has been over standard of 0.3 mg/l and much higher than that in Balisprings of Sanggalangit, Pemuteran and Banyuwedang (0.1567 – 0.1817 mg/l) also overiron content in Bali lakes that below 0.150 mg/l. Conductivity content in the springs(126-275 ?S/cm), is consistent to the total suspended solid (TDS) of 150-290 mg/l inwhich at the high TDS, the conductivity is high as well and vice versa. At Buyan spring,pH value is the lowest and a bit acid (6.07) that closes related to the highest content ofsulfite (15.55 mg/l). Nitrate at the springs (3.388 – 6.735 mg/l) are high and much higherthan that in Bali springs of Sanggalangit, Pemuteran and Banyuwedang (0.422 - 0.503mg/l) also over than nitrate content in Beratan, Buyan and Tamblingan lakes that below2.5 mg/l.